2008
DOI: 10.1007/s10519-008-9222-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Genetic Effects on the Acoustic Startle Reflex and its Sensitization in C3H/HeN, DBA/2JHd and NMRI Mice Following Blastocyst Transfer

Abstract: In the present study, reciprocal embryo transfers were conducted to examine genetic and maternal effects on the baseline and fear-sensitized acoustic startle response (ASR) in the two inbred strains C3H/HeN and DBA/2JHd and the outbred strain NMRI. The largest differences in the ASR were found in untreated strains (effect size 0.6). The transfer procedure per se had a significant effect on the behavior of NMRI mice resulting in a reduction in the baseline, and an increase in the fear-sensitized ASR. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…This observation is in line with a study comparing maternal and genetic effects using different mouse strains. It was shown that foot shock sensitization is mainly influenced by genetic factors, whereas startle reactivity is affected both by genetic and prenatal and postnatal factors (Rose et al 2008). Accordingly, mouse strains may differ in the magnitude of the response and also in the time frame in which the shock sensitization occurs (Dirks et al 2001a), as was also found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in line with a study comparing maternal and genetic effects using different mouse strains. It was shown that foot shock sensitization is mainly influenced by genetic factors, whereas startle reactivity is affected both by genetic and prenatal and postnatal factors (Rose et al 2008). Accordingly, mouse strains may differ in the magnitude of the response and also in the time frame in which the shock sensitization occurs (Dirks et al 2001a), as was also found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that mouse strains vary widely in their emotional reactivity (Bothe et al 2005; Crawley et al 1997; van Bogaert et al 2006), as well as in startle reactivity (Pietropaolo and Crusio 2009; Rose et al 2008) and PPI (Millstein et al 2006; Paylor and Crawley 1997). In the present study, comparable strain differences were observed.…”
Section: Discussionmentioning
confidence: 99%
“…If the prepulse is temporally coupled with an aversive stimulus for a number of times, increased ASR amplitude and reduced PPI have been observed (Davis et al 1993, Falls et al 1997, Heldt et al 2000; McCaughran et al 2000; Dirks et al 2001; Balogh et al 2002; Rose et al 2008; Li et al 2009). It is a common observation that ASR, PPI, and how the modification of the response changes over time differs between mouse strains and individuals of the same strain (e.g., Bullock et al 1997; Pilz et al 2004; Simons-Weidenmaier et al 2006; Typlt et al 2013a Yee et al 2005, and see section 4.1 Strain).…”
Section: Non-associative and Associative Learning Effectsmentioning
confidence: 99%
“…Variables such as maternal separation, rearing, and other social effects may influence the expression of ASR and PPI (Francis et al 2003; Millstein et al 2006; Rose et al 2008). Social isolation produces PPI deficits in at least four strains of mice (C57BL6/J and 129T2-Varty et al 2006; ddY-Sakaue et al 2003; C57BL/6-Pietropaolo et al 2008; C57BL6/J-Martin and Brown 2010).…”
Section: Other Considerationsmentioning
confidence: 99%
“…Two methods have been used with mice: embryo transfers (Denenberg, Hopligh, & Mobraaten, 1998) and grafted ovaries (Carlier, Roubertoux, & Pastoret, 1991), both in conjunction with the adoption method. In short, many studies conducted on rodents concluded that genetic variation is linked to differences in a large range of behavioral traits, including learning, in conjunction or interaction with the maternal environment (Carlier et al, 1992, 1999 – see Rose, Röhl, Hanke, Schwegler, & Yilmazer-Hanke, 2008 for recent examples.…”
Section: Genetics and Cognition Before The Sequencing Of Mammalian Ge...mentioning
confidence: 99%